Diathermy versus scalpel incisions in elective abdominal surgery: a comparative study - Nandurkar, Vikranth S.; K., Mohan Kumar; M., Prakash; S., Suma (International Surgery Journal, 2018)
Background: Scalpel incisions produce little damage to surrounding tissues. There has been a widespread use of diathermy for hemostasis but fear of production of large scars and improper tissue healing has restricted their usage in making skin incisions. Use of diathermy in skin incisions reduces bleeding and makes the incision quicker, but there are no differences in wound burst strength. Objective of the study was to compare the use of diathermy and scalpel incisions in elective abdominal surgery’s to see the variations in incisional time, blood loss during incision, postoperative pain and wound complications Methods: This was a prospective randomized study, which included patients above 18 years who underwent elective abdominal surgery. The patients were randomly included into Group A or Group B. In Group A incision was made with a scalpel and in group B with diathermy. Data was analyzed for incisional time, blood loss during incision, postoperative pain and wound complications. Results: There was a significant increase in mean time taken for incision in Group A when compared to Group B. Mean incision blood loss was found to be significantly higher in group A compared to group B patients. Postoperative pain was significantly higher in group A (p value <0.05) on postoperative day 1. Among wound complications, no statistically significant differences were seen between the two groups. Conclusions: Electrocautery incisions were safe, less time consuming, reduced blood loss and had less postoperative pain. We conclude that diathermy could be accepted as an alternative method for surgical skin incisions.